2007
DOI: 10.1038/sj.gt.3302945
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible micellar nanovectors achieve efficient gene transfer to vascular lesions without cytotoxicity and thrombus formation

Abstract: Gene therapy, a promising treatment for vascular disease, requires appropriate gene vectors with high gene transfer efficiency, good biocompatibility and low cytotoxicity. To satisfy these requirements from the approach of nonviral vectors, a novel block copolymer, poly

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 35 publications
1
70
0
Order By: Relevance
“…22,23 Our previous study indeed showed that administration of PEG-PAsp(DET) micelles into rabbit carotid artery accomplished appreciable gene transfer to the artery, without occlusion by thrombus formation. 20 In contrast, the same study revealed that polyplex made from polyethyleneimine markedly caused thrombus occlusion after intra-arterial application, indicating that positively charged polyplex potentially underwent aggregation with plasma proteins and blood cells. As thrombus formation possibly interferes with the process of gene transfer and further impairs vascular functions, it appears necessary for gene vectors for the treatment of vascular diseases to possess non-thrombogenic properties, like PEG-PAsp(DET) micelles.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…22,23 Our previous study indeed showed that administration of PEG-PAsp(DET) micelles into rabbit carotid artery accomplished appreciable gene transfer to the artery, without occlusion by thrombus formation. 20 In contrast, the same study revealed that polyplex made from polyethyleneimine markedly caused thrombus occlusion after intra-arterial application, indicating that positively charged polyplex potentially underwent aggregation with plasma proteins and blood cells. As thrombus formation possibly interferes with the process of gene transfer and further impairs vascular functions, it appears necessary for gene vectors for the treatment of vascular diseases to possess non-thrombogenic properties, like PEG-PAsp(DET) micelles.…”
Section: Discussionmentioning
confidence: 94%
“…The balloon was inflated at physiological pressure and passed through the common carotid artery three times with constant rotation. 20 At 21 days after balloon injury, polyplex micelles were administered into the common carotid artery, in which neointimal hyperplasia had been induced. pCAccluc+ was complexed with cRGD-PEG-PAsp(DET) or PEG-PAsp(DET) at N/P ratio of 5.…”
Section: Animal Model and Evaluation Of Gene Expression Efficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…67,70,71 Polymeric micelles Polyplex micelles composed of PEG-polycation block copolymers and pDNA have been widely used as nonviral vectors with a potential for systemic applications. [72][73][74] The size of these polyplex micelles is B100 nm, which is considered to be optimal for systemic administration. Moreover, these polyplex micelles contain a biocompatible PEG shell layer, which prevents any sort of nonspecific interaction with blood components.…”
Section: Rgd-peg-sucmentioning
confidence: 99%